Cohen’s Kappa Agreement among Multiple Raters in Determining Factors that Influence MTUN Academics on Data Sharing (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Data sharing has become prominent nowadays. On the other hand, the universities produce a vast amount of data but most of these data are kept in a silo, not available, and confidential. This study will investigate the factor that influences Malaysian Technical University Network (MTUN) academics on data sharing. The questionnaire was constructed by adapting the questionnaire from the previous study. There are four (4) constructs that determine data sharing; technological, organizational, environmental, and individual. There are five (5) experts have been appointed to validate the questionnaire. The validation is needed as the questionnaire adapted needs to undergo some amendment to suit the research domain. Once the experts have given their opinion regarding the item’s relevance to measuring the constructs, then the calculation of Cohen’s Kappa interrater index is conducted. Cohen’s Kappa interrater index is used to measure the consensus of all experts on the respective items. This paper will explain in detail how the Cohen’s Kappa interrater index is conducted and how the relevancy of the items can be measured and achieved. Only when the interrater index is achieved, then it can be assumed that the questionnaire has been validated by the experts and ready to be distributed to MTUN academics for pilot study purposes.